Morbidity after Total Gastrectomy: Analysis of 238 Patients - Selby, Luke V; Vertosick, Emily A; Sjoberg, Daniel D; Schattner, Mark A; Janjigian, Yelena Y; Brennan, Murray F; Coit, Daniel G; Strong, Vivian E (Journal of the American College of Surgeons, 2015)
Surgical quality improvement requires well-defined benchmarks and accurate reporting of postoperative adverse events, which have not been well defined for total gastrectomy. Detailed postoperative outcomes on 238 patients who underwent total gastrectomy with curative intent, from 2003 to 2012, were reviewed by a dedicated surgeon chart reviewer to establish 90-day patterns of adverse events. Of the 238 patients with stage I to III gastric adenocarcinoma who underwent curative-intent total gastrectomy, the median age was 66 years, and 68% were male. Median body mass index was 28 kg/m(2), and 68% of patients had at least 1 medical comorbidity. Forty-three percent of our patients received neoadjuvant chemotherapy, and 34% received postoperative adjuvant chemotherapy. Over the 90-day study period, 30-day mortality was 2.5% (6 of 238), and 90-day mortality was 2.9% (7 of 238). At least 1 postoperative adverse event was documented in 62% of patients, with 28% of patients experiencing a major adverse event requiring invasive intervention. The readmission rate was 20%. Anemia was the most common adverse event (20%), followed by wound complications (18%). The most common major adverse event was esophageal anastomotic leak, which required invasive intervention in 10% of patients. This analysis has defined comprehensive 90-day patterns in postoperative adverse events after total gastrectomy with curative intent in a Western population. This benchmark allows surgeons to measure, compare, and improve outcomes and informed consent for this surgical procedure.